ANALISIS ANGGARAN KAS SEBAGAI ALAT PERENCANAN DAN PENGENDALIAN KAS PADA PT PELABUHAN INDONESIA IV CABANG BITUNG - Saipi, Raquel Amelia; Tinangon, Jantje J.; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
PT Pelabuhan Indonesia IV Branch Bitung uses the cash budget as their management tool, for the planning and control of the company's cash in achieving the success of the objectives to be achieved by the company. The purpose of this research is to know how cash budget as a planning and control tools cash in PT Pelabuhan Indonesia IV Branch Bitung with observation period of cash budget in 2015, 2016, and 2017. In this research, using descriptive method by collecting information from research result then analyze and draw conclusion from research, method of collecting information in this research by direct interview with finance section about process of preparing cash budget. The results show that the cash budgeting process in PT Pelabuhan Indonesia IV Branch Bitung uses a buttom up budgeting approach where the budget is prepared and prepared by the parties who will implement the budget. The causes of the difference (variance) between the budget and the realization of the cash budget are internal and external factors of the firm. Planning the cash budget by estimating the cost and analysis of the company's activities and for controlling its cash budget in the form of control over good deviations is favorable or unfavorable as well as revisions to deviations that occur.Keywords: Cash Budget, Planning, Controlling